Artificial intelligence techniques for implementation of intelligent machining - Abdul Wahab Hashmi, Hashmi; Harlal Singh Mali, Harlal Singh; Anoj Meena, Anoj; Khilji, Irshad Ahamad; Mohammad Farukh, Hashmi; Siti Nadiah, Mohd Saffe (Science Direct, 2022)
For the past few years, the rapid progress and development of artificial intelligence (AI) based technologies have been analyzed for the applications of the intelligent manufacturing industry, i.e., industry 4.0. this has triggered a valuable transformation in means, models, and ecosystems within the manufacturing industry and AI development. With the advancement in manufacturing technology, there is a need to execute these technologies and AI more efficiently and cost-effectively. It can be possible by combining traditional manufacturing and machining technologies with recently developed intelligent manufacturing technologies comprising hardware and software techniques. This review paper discusses various AI implementation-based intelligent manufacturing industries with their architecture and technology systems based on the integration of AI with manufacturing and information communication. Furthermore, AI-based manufacturing application, their implementation, and current development in intelligent manufacturing have also been discussed.